Enterprise Architecture Data pada Hotel ABC - Stephanie Soesatyo; Adi Wibowo; Andreas Handojo (Jurnal Infra, 2015)
Hotel ABC is a company engaged in hospitality management, i.e. room rental, rental of meeting rooms and coffee shop. Hotel ABC has a branch that has the same specifications of the hotel. In business process, Hotel ABC has information systems to support existing business processes. However, existing information systems have not been integrated as a whole. Based on the condition stated above, analysis and design of enterprise architecture information system is created for the company. The process begins with analyzing the business model and business strategy of the company. Then analyze the conditions of current information technology in enterprise, problems faced and the requirements of future information technology. After that, the design of data architecture, application architecture and technology architecture are built in accordance with the objectives, business strategy and business processes are made.The design of the data architecture for enterprise consists of several subsystems. Application architecture consists of several major and supporting applications. Technology architecture using Client / Server Architecture and Service Oriented Architecture Pattern.